Tuning dielectric and magnetic properties of complex perovskites PbB'1/2B"1/2O3 and solid solutions by varying the degree of compositional (chemical) ordering of B' and B" ions. Issue 1 (19th May 2021) - Raevski, I. P.; Kubrin, S. P.; Gusev, A. A.; Pushkarev, A. V.; Olekhnovich, N. M.; Radyush, Y. V.; Raevskaya, S. I.; Titov, V. V.; Permiakov, A. Y.; Malitskaya, M. A.
Abstract: Methods of changing the compositional (chemical) ordering degree S of B' and B" cations in Pb B' 1/2 B" 1/2 O3 perovskites and some BiFeO3 - PbFe1/2 B" 1/2 O3 solid solutions and the effect of such ordering/disordering on their dielectric and magnetic properties are discussed. High-energy mechanical activation appears to be a very effective method of varying the temperatures of ferroelectric and magnetic phase transitions in complex perovskites. To explain the results obtained, one needs to take into account the changes not only of the long-range ordering of B' and B" ions, but also of the short range ordering.